2013
DOI: 10.3758/s13420-013-0104-z
|View full text |Cite
|
Sign up to set email alerts
|

The informational value of contexts affects context-dependent learning

Abstract: In two predictive-learning experiments, we investigated the role of the informational value of contexts for the formation of context-dependent behavior. During Phase 1 of each experiment, participants received either a conditional discrimination in which contexts were relevant (Group Relevant) or a simple discrimination in which contexts were irrelevant (Group Irrelevant). Each experiment also included an ABA renewal procedure. Participants received Z+ in context A during Phase 1, extinction of Z in context B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 34 publications
(60 reference statements)
4
36
0
1
Order By: Relevance
“…Despite obvious differences in processing requirements, previous studies highlighted the parallels between context-related extinction learning with and without a fear component: In both, fear (for review see Bouton, 2002, 2004) and non-fear related extinction (Rosas and Callejas-Aguilera, 2006; Rosas et al, 2006; Ungör and Lachnit, 2006; Üngör and Lachnit, 2008; Lucke et al, 2013, 2014), the renewal effect has been demonstrated. Moreover, recent imaging/lesion studies emphasized involvement of similar brain regions in both types of extinction learning, in animals as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Despite obvious differences in processing requirements, previous studies highlighted the parallels between context-related extinction learning with and without a fear component: In both, fear (for review see Bouton, 2002, 2004) and non-fear related extinction (Rosas and Callejas-Aguilera, 2006; Rosas et al, 2006; Ungör and Lachnit, 2006; Üngör and Lachnit, 2008; Lucke et al, 2013, 2014), the renewal effect has been demonstrated. Moreover, recent imaging/lesion studies emphasized involvement of similar brain regions in both types of extinction learning, in animals as well as in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the best known anatomical connections of Crus II, however, is that with dlPFC [39]. According to current learning theories of extinction and renewal, the unexpected omission of the unconditioned stimulus (US) at the beginning of extinction shifts attention to the context [40,41]. Attention shifting is a known function of the dlPFC [42].…”
Section: Discussionmentioning
confidence: 99%
“…With a design in which acquisition, extinction and test phase are run back-to-back without breaks in between, a renewal effect can be reliably evoked, as demonstrated in several studies using this design of a predictive learning task (Lucke et al, 2013;Nelson and Callejas-Aguilera, 2007;Rosas and Callejas-Aguilera, 2006;Lachnit, 2006, 2008).…”
Section: Predictive Learning Taskmentioning
confidence: 96%